In vivo analyses of RNA polymerase I termination in Schizosaccharomyces pombe. - Melekhovets, Y F (1997)
Recent studies on the termination of rDNA transcription by RNA polymerase I in Saccharomyces cerevisiae and Schizosaccharomyces pombe have suggested a more complex mechanism then previously described in higher eukaryotes. Termination appears to occur when a DNA-bound Reb1 protein molecule induces polymerase to pause in the context of a release element [see Reeder,R.H. and Lang,W. (1994) Mol. Microbiol ., 12, 11-15]. Because these conclusions in yeast were based entirely on in vitro analyses, we have examined the same termination process in S.pombe by expressing targeted mutations in vivo . S1nuclease protection studies indicate three tandemly arranged termination sites with most transcripts very efficiently terminated at the first site, 267 nt after the 3' end of the mature 25S rRNA sequence. Termination at each site is mediated by conserved terminator elements which bear limited sequence homology with that of mouse and also can be identified in S.cerevisiae . Removal of the first terminator element transfers dominance to the second site and construction of a new single terminator element at +150 still results in efficient termination and rRNA processing without a need for an additional upstream element. Genomic 'footprint' analyses and gel retardation assays confirm a process mediated by a strongly interacting protein factor but implicate an alternate binding site. Removal of the 5' flanking sequence or structure also had no effect on the site or efficiency of termination. Taken together the results in vivo suggest that the termination process in this fission yeast more strongly resembles the single element-mediated mechanism initially reported in mouse and is not dependent on additional upstream sequence as first reported in S.cerevisiae and postulated to function in general.